2014
DOI: 10.1039/c4sm01112k
|View full text |Cite
|
Sign up to set email alerts
|

A new microscopic insight into membrane penetration and reorganization by PETIM dendrimers

Abstract: Dendrimers are highly branched polymeric nanoparticles whose structure and topology, largely, have determined their efficacy in a wide range of studies performed so far. An area of immense interest is their potential as drug and gene delivery vectors. Realizing this potential, depending on the nature of cell surface-dendrimer interactions, here we report controlled model membrane penetration and reorganization, using a model supported lipid bilayer and poly(ether imine) (PETIM) dendrimers of two generations. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 68 publications
3
40
0
Order By: Relevance
“…We would like to add here that this was more a proof‐of‐principle experiment which demonstrated the possibility of creating such biomimetic membrane and polymer grafted nanoparticles hybrids for enhancing detection sensitivity of dyes using the plasmon resonance of the nanoparticles. More systematic study in terms of optimizing the nanoparticles concentration, as we have shown for dendrimer‐membrane hybrids or applying this to other types of plasmonic nanoparticles or polymers or even different lipid compositions would further improve the versatility of these templates.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We would like to add here that this was more a proof‐of‐principle experiment which demonstrated the possibility of creating such biomimetic membrane and polymer grafted nanoparticles hybrids for enhancing detection sensitivity of dyes using the plasmon resonance of the nanoparticles. More systematic study in terms of optimizing the nanoparticles concentration, as we have shown for dendrimer‐membrane hybrids or applying this to other types of plasmonic nanoparticles or polymers or even different lipid compositions would further improve the versatility of these templates.…”
Section: Resultsmentioning
confidence: 98%
“…To quantify exactly how the biomimetic lipid membranes help the PGNPs to modify the dye molecule emission enhancement, and especially to obtain a microscopic picture of the PGNP configuration on the lipid bilayers, we further decided to use DMPC SLBs as a biomembrane platform to repeat some of the experiments performed with DMPC SUVs. The DMPC SLBs were prepared using the well established Langmuir–Blodgett (LB) technique and transferred on glass slides (Hecht‐Assistent, Germany), as described in methods and elsewhere, at surface pressure of 33–35 mN m −1 . Figure a–c shows the confocal images (Leica SP5 Confocal Microscopy, Germany) of such SLBs incubated first with PGNPs at appropriate concentrations and subsequently with Rh and CY5 dye molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dinoflagellates of the genus Hematodinium infect over 40 species of marine crustaceans. Since the initial description of this parasite in France in the 1930s [ 1 ], it appears to have spread globally, causing economic loss in some species, including Tanner crabs ( Chionoecetes bairdi ) in Alaska [ 2 ], blue crabs ( Callinectes sapidus ) in the United States [ 3 ], edible crabs ( Cancer pagurus ) and Norway lobsters ( Nephrops norvegicus ) in Europe [ 4 – 7 ], sand crabs ( Portunus armatus ) in Australia [ 8 ], and Chinese swimming crabs ( Portunus trituberculatus ) in northern China [ 9 ]. Because this disease is thought to be fatal, it may be of great significance to the sustainability of both captive shellfish fisheries and aquaculture [ 10 , 11 ].…”
Section: Hematodinium Infections: a Problem For The Sustainamentioning
confidence: 99%